Socio-Cultural Dynamics in K. K. Karmacharya’s Artworks - Sharma, Yam Prasad (AMC Multidisciplinary Research Journal, 2022)
Contemporary Nepali artist K. K. Karmacharya's artworks present socio-cultural issues of the contemporary context of Nepal. The life of the people, their context and activities vividly appear on the canvas. The paintings explore spiritual themes, cultural rituals and social activities in the community. The compositions not only represent the external world but also respond to the situation in visual form. Nepali tradition and ordinary works get space on his canvas. Some art forms mirror the society as it is and some works take corrective measures. They criticize the people and society from distance. The works are connected to the artist, his surroundings and his living experience. This study follows a qualitative approach for research since the artworks can be interpreted in multiple ways.